Ice drift in Peter the Great Bay - Vyacheslav A. Dubina; Vladimir V. Plotnikov; Nina S. Kot (Известия ТИНРО, 2014)
Dynamics of the sea ice cover in Peter the Great Bay is considered, for the first time for its whole area, on the base of satellite images received in 2004-2011 from the spectroradiometers MODIS mounted on the satellites Terra and Aqua. High spatial resolution maps of the ice drift are constructed for various wind conditions. Mean values of the drift velocity and wind coefficient are calculated for four parts of the Bay. In usual conditions of winter monsoon, the ice in the central part of Peter the Great Bay drifts southward with the velocity 0.5-0.6 m/s with deviation from the wind direction about 40° to the right; the ice at the western coast drifts along the island chain with the velocity 0.1-0.4 m/s under wind of any direction in the quadrant from northwest to northeast.